2000
DOI: 10.1007/s101520050011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the polychaete Nereis diversicolor on the distribution and transplanting success of Zostera noltii

Abstract: Loss of saltmarsh vegetation in south-east England is a significant problem for conservation and coastal defence. The losses of vegetation began in the 1930s with the loss of intertidal Zostera marina and have continued more recently. Some preliminary trials at reestablishing Zostera in some estuaries of Essex have not been successful. This paper addresses the hypothesis that the infauna, particularly the polychaete Nereis diversicolor, may restrict natural colonisation by Zostera and reduce the success of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…Surprisingly, however, these papers neglect the potential restoration benefits of the removal of negative interactions originating from ecosystem engineers, despite the fact that such interactions can play an important role in marine habitats (Rhoads and Young 1970, Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007. In this study, we show that suppressing such negative ecosystem-engineering effects could be a useful approach in restoration and conservation efforts by giving at least a better start during the initial establishment phase.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Surprisingly, however, these papers neglect the potential restoration benefits of the removal of negative interactions originating from ecosystem engineers, despite the fact that such interactions can play an important role in marine habitats (Rhoads and Young 1970, Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007. In this study, we show that suppressing such negative ecosystem-engineering effects could be a useful approach in restoration and conservation efforts by giving at least a better start during the initial establishment phase.…”
Section: Discussionmentioning
confidence: 65%
“…For example, this has been shown for the negative effect of deposit feeders on filter feeders by making sediment more erosive, causing filter feeding to be hampered by more turbid water (i.e., trophic group amensalism; Rhoads and Young 1970). Several studies have also demonstrated that negative interactions between benthos and vegetation can be very strong (Philippart 1994, Hughes et al 2000, Hughes and Paramor 2004, Siebert and Branch 2006, Berkenbusch et al 2007, van Wesenbeeck et al 2007). For instance, ''biomechanical warfare'' between ecosystem-engineering salt marsh vegetation and infauna can cause a bimodal species distribution on the salt marsh-mudflat interface, as bioturbation prevented plant colonization in the invertebrate-dominated state and invertebrates were excluded by sediment compaction in the plantdominated state (van Wesenbeeck et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hootsmans et al (1987) observed maximum recruitment at 10 psu and no recruitment above 30 psu in natural populations. Likewise, under experimental conditions, the highest levels of germination were observed at salinity levels of between 1 and 10 psu with no germination above 20 psu (Hughes et al 2000).…”
Section: Conservation Implicationsmentioning
confidence: 95%
“…Paramor & Hughes (2004) presented evidence that loss of saltmarsh vegetation from the pioneer zone, and by internal erosion of saltmarsh creeks, was exacerbated by bioturbation and herbivory by the infauna, particularly the ragworm Nereis diversicolor. N. diversicolor may occur high in the intertidal zone where they are predominantly surface deposit-feeders and consume microphytobenthos (Smith et al 1997), filamentous algae (Hughes 1999) and the seeds and seedlings of saltmarsh plants (Hughes et al 2000, Paramor & Hughes 2004. Bioturbation by the amphipod Corophium volutator may also destabilise the sediment and prevent establishment of seedlings of saltmarsh plants (Gerdol & Hughes 1993).…”
Section: Introductionmentioning
confidence: 99%